Pension Obligations and the Bond Credit Market: An Empirical Analysis of Accounting Numbers - Maher, John J. (The Accounting Review, 1987)
[The purpose of this study is to examine the importance and measurement of net pension variables in the bond rating decision. This paper uses SFAS No. 36 pension footnote disclosures to develop measures of the net pension asset (liability) to be included as an independent variable in a bond rating prediction model. Multiple measures of the pension obligation (asset) are calculated in an attempt to determine which, if any, of these measures are found to be a significant factor in bond ratings. Measures used include the pension obligation actually reported by the corporation in its annual report as well as recalculated obligations based on cross-sectionally standardized interest discount rates. Results indicate a lack of significance of any pension measure in 1980. In 1981 and 1982, pension measures calculated using standardized interest rates are found to be significant in the bond rating decision. In no year was the coefficient for the pension measure actually disclosed by the company in its annual report significant. Further analyses on subgroups indicated that the pension variable was highly significant in 1981 and 1982 for net pension liability companies when the obligation was discounted at the average interest rate, but not significant in those years for net pension asset companies.]